2017
DOI: 10.4174/astr.2017.93.5.266
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic risk factors for lymph node metastasis in patients with T1 colorectal cancer

Abstract: PurposeEvaluating the risk of lymph node metastasis (LNM) is critical for determining subsequent treatments following endoscopic resection of T1 colorectal cancer (CRC). This study analyzed histopathologic risk factors for LNM in patients with T1 CRC.MethodsThis study involved 745 patients with T1 CRC who underwent endoscopic (n = 97) or surgical (n = 648) resection between January 2001 and December 2015 at the National Cancer Center, Korea. LNM in endoscopically resected patients, which could not be evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 20 publications
2
45
0
1
Order By: Relevance
“…This finding agrees with three recently published studies manifesting that lymphatic invasion is causally associated with the risk of LNM in CRC [47][48][49]. Tumor budding is recognized as a negative prognostic risk factor for LNM in CRC, and our findings are concordant with previous studies [50][51][52]. Individual component studies vary in their definitions of tumor budding (e.g., how many cancer cells comprise a tumor bud, and how many buds signify tumor budding) and vary in the pathologic staining methods to detect tumor budding (e.g., hematoxylin and eosin [H&E], immunohistochemistry [IHC]).…”
Section: Discussionsupporting
confidence: 94%
“…This finding agrees with three recently published studies manifesting that lymphatic invasion is causally associated with the risk of LNM in CRC [47][48][49]. Tumor budding is recognized as a negative prognostic risk factor for LNM in CRC, and our findings are concordant with previous studies [50][51][52]. Individual component studies vary in their definitions of tumor budding (e.g., how many cancer cells comprise a tumor bud, and how many buds signify tumor budding) and vary in the pathologic staining methods to detect tumor budding (e.g., hematoxylin and eosin [H&E], immunohistochemistry [IHC]).…”
Section: Discussionsupporting
confidence: 94%
“…[197][198][199][200][201][202] Multivariate analyses have shown that poor histologic types (poorly differentiated adenocarcinoma, signet ring cell carcinoma, mucinous carcinoma) have increased ORs (2.93-45.9) for lymph node metastasis compared with well differentiated adenocarcinomas. [203][204][205] Four meta-analyses also showed early colorectal cancers with poor histologic types to have an increased risk of lymph node metastasis with ORs ranging between 4.78 and 8.27. 8,[206][207][208] Well differentiated intramucosal colorectal cancer does not metastasize to the lymph nodes, whereas 6%-20% of early colorectal cancers that invade the submucosa metastasize to the lymph nodes.…”
Section: Statement G13mentioning
confidence: 99%
“…[210][211][212] The risk of lymph node metastasis increases in proportion to the depth of submucosal invasion determined by these classification methods (Haggitt level 4 and Kudo sm2-3). [197][198][199]205,209,213,214 In studies that measured the absolute depth of submucosal invasion from the muscularis mucosa and evaluated the risk of lymph node metastasis, depth of vertical invasion of ≥1,000 μm of nonpedunculated cancer were associated with the risk of lymph node metastasis, and the risk increased in proportion to the depth of invasion. 201,203,[215][216][217][218][219] In meta-analyses evaluating the risk of lymph node metastases in colorectal cancer, depth of submucosal invasion of ≥1,000 μm increased the OR of lymph node metastasis to 3.0-5.93.…”
Section: Statement G13mentioning
confidence: 99%
See 1 more Smart Citation
“…An isolated cell or a small cluster of fewer than 5 carcinoma cells in the invasive front was defined as a budding focus, with positive tumor budding defined as more than 10 budding foci viewed at 200-fold magnification [8]. According to our previous study, the risk factors for lymph node metastasis (LNM) contain deep SM invasion (sm2 or sm3), vascular invasion, high histological grade, budding [9], and pathological diagnoses were performed by a board-certified pathologist (HJC).…”
Section: Patient Recruitment and Stratificationmentioning
confidence: 99%